Exercise training partly ameliorates cardiac dysfunction in mice during doxorubicin treatment of breast cancer - Tytti-Maria Uurasmaa; Pauline Bourdin; Wail Nammas; Shiva Latifi; Heidi Liljenbäck; Antti Saraste; Olli Eskola; Johan Rajander; Anne Roivainen; Helene Rundqvist; Anu Autio; Ilkka Heinonen; et al. (Journal of Translational Medicine)
Abstract Introduction Doxorubicin is a chemotherapeutic drug used to treat various cancers. Exercise training (ET) can attenuate some cardiotoxic effects of doxorubicin (DOX) in tumor-free animals. However, the ET effects on cardiac function and glucose metabolism in DOX-treated breast cancer models remain unclear. Objectives This study investigated ET-induced structural, functional, vascular, oxidative stress, and plausible glucose uptake alterations of the left ventricle (LV) in a murine breast cancer model during DOX treatment. Methods Female FVB/N-mice were divided to tumor-free groups with or without voluntary wheel-running ET and those inoculated subcutaneously with mammary tumor-derived I3TC-cells with or without exercise or DOX treatment (5 mg/kg/week). Mice underwent 2-[18F]fluoro-2-deoxy-D-glucose positron emission tomography and echocardiography after two and four DOX-doses. The cardiac histology, oxidative stress, maximal metabolic enzyme activities, and mitochondrial respiration were analyzed. Results DOX increased LV glucose uptake (LVGU) and mitochondrial uncoupling and decreased running activity, LV-weight, and ejection fraction (EF). In DOX-treated group ET blunted the increase in LVGU, increased LV-weight and EF, and lowered LV lactate dehydrogenase activity. DOX-treated exercised mice did not differ from tumor-bearing group without DOX in LVGU or from the tumor-free ET-group in LV-weight or EF whereas unexercised DOX-treated group did. ET also increased LV citrate synthase activity in tumor-bearing animals. There was an inverse association between LVGU and EF and LV-weight. Conclusion In a murine breast cancer model, voluntary ET moderated DOX-induced cardiotoxicities such as increased LVGU, LV-atrophy and decreased EF. This suggests that ET might benefit patients with cancer undergoing doxorubicin treatment by mitigating cardiotoxicity.